Applying Balanced Scorecard For Performance Measurement At Batam Type B Customs And Excise Facilities - Agung Maulana Syahrudin; Hanif Kurniadi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This paper elucidates the implementation of the Balanced Scorecard in performance measurement at the Type B Customs and Excise Operations Base in Batam. The research aims to comprehend the application of organizational performance management through the Balanced Scorecard method at this facility, considering four perspectives: customer perspective, stakeholder perspective, learning & growth perspective, and internal processes. These perspectives culminate in the final result manifested as organizational performance value. The methodology employed in this academic study is a qualitative descriptive method, grounded in facts and data acquired from literature reviews, interviews, and observations. The findings of this research indicate that the organizational performance value attained by the Type B Customs and Excise Operations Base in Batam for the fiscal year 2022 exhibits commendable indicators, albeit suggesting the need for improvement in the customer perspective.